China-ASEAN Environment Outlook 1 (CAEO-1) Towards Green Development. (Springer Singapore, 2018)
This book presents a comprehensive analysis of the status and progress of China-ASEAN green development and examines the common development issues in China and ASEAN Member States (AMSs). It also explores development trends within the framework of global and regional environmental governance and discusses the approaches towards green development in China and AMSs, offering its own definition of green development and using a "pressure-state-response" (PSR) model to build a framework for assessing green development. The book includes typical policy measures and numerous practices for green development in China and AMSs in the form of tables, figures and boxes. Based on detailed analysis, it argues that the global 2030 Agenda for Sustainable Development brings significant opportunities to China and AMSs, that the ongoing pragmatic cooperation should be further advanced, and that a connection between the Belt and Road Initiative and green ASEAN Community should be established to achieve regional sustainable development. As such it furthers readers' understanding of environment and development and practical policy advice for promoting China-ASEAN cooperation on environment and green development. Intended for decision makers from the government, business sector, and civil societies who are working to boost green development and China-ASEAN cooperation, it is also a valuable resource for government officials, researchers and non-experts interested in creating a balanced relationship between the environment and development.